Livelihood Strategies in Southern India Conservation and Poverty Reduction in Forest Fringes - Purushothaman, Seema.; Abraham, Rosa. (Springer India : Imprint: Springer, 2013)
This volume is a compilation of essays that focus on livelihood issues faced by forest communities of the southern Western Ghats region of India. Communities living along the fringes of forests are, more often than not, overlooked in academic and policy discussions. However, they face considerable pressures, being sandwiched between conservation endeavours and the forces of urbanization and commercialization. The chapters in this book provide an insight into the kinds of livelihood issues these communities face and the potential means that can be adopted to sustain these livelihoods. This volume provides a unique alternative perspective by locating livelihood issues within socio-ecological-economic narratives of communities living at the intersection of the three southern Indian states of Karnataka, Kerala and Tamil Nadu, and suggests directions for policies to address these challenges.